ANALISIS PRESTASI BELAJAR SISWAKELAS IV, V, VI SDN. 010 BAGAN NIBUNG - Umari, Tri Umari Tri; ', Juliati; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Which aims to analyze student achievementgradeIV, V, VISDN. 010BaganNibunggenerallybased onparental education, based on thework of parents, by genderandbyethnicity. MethodsThis was a descriptivestudythatexaminedstudent achievement bydescribing the object. Toolpiece ofdata usedin this studyis theaveragevalue ofStudents(Value Report Card).The populationof thisresearchis classIV, V, VISDN.010BaganNibungtotaling80students. Andanalysisfoundthatstudent achievementvariesseengenerallybased onparental education, based on thework of parents, by gender andethnicity. Recommended to theschoolandteachersBKtobe ableto stay abreast ofstudent achievement. Forparents toguide their childrencan  achievebetterlearningachievement.ForresearchersstudentachievementinSDN.010BaganNibungandbothgroupsandwere maintainedandfurther improved. Keywords : Achievement, Study, Student.